TOKSISITAS DAN AKTIVITAS GASTROPROTEKTIF EKSTRAK TANGKAI TALAS (Colocasia esculenta L. Schott) Pengujian Aktivitas Toksik dan Gastroprotektif Ekstrak Tangkai Talas terhadap Tikus Putih Galur Wistar (Rattus norvegicus) yang Diinduksi Aspirin - Aiman Hilmi Asaduddin (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2018)
Background : Peptic ulcer is one of the world's major gastrointestinal disorders and affecting 10% of the world population. The drugs available in the market are often associated with side effects. Thus, it is needed to identify more effective and safe anti-ulcer agents. However, taro stem (Colocasia esculenta L. Schott) have some chemical compounds that hypothesized have gastroprotective activity and low toxicity level. Goals : to determine toxicity level and efect of taro stem extract (TSE) in gastroprotective activity in the gaster of Rattus norvegicus. Method : to determine the toxicity of TSE, this present study used Brine Shrimp Lethality Test (BSLT) and acute oral toxicity assay (OECD 423). Then, the gastroprotective effect examined by phytochemical assays, antioxidant activity, and histopathological examination. The TSE gastroprotective experiment in aspirin induced rats is divided into 4 groups (50, 100, 200, and 400 mg/kgBW) with omeprazole and sucralfate as reference controls. Result : The phytochemical test showed that TSE positively contained flavonoid, terpenoid, saponin, and steroid. The extract had antioxidant activity measured 675.283 pg/ml. Based on data, TSE had no effect in toxicity assays. BSLT result showed LC50 of TSE was 7311.39 ppm which have a very low toxicity. Acute toxicity showed no injury and mortality in rats. The histopathological examination revealed that aspirin shows severe damage in gastric mucosa. TSE 50, 100, and 200 mg/kgBW did not show significant difference. TSE treatment significantly suppressed the mucosa disruption in 400 mg/kg dose, inhibit edema the infiltration of leucocyte, and reduce the neutrophil infiltration into ulcerated tissue. TSE treatment also revealed increasing of surface mucosal glycoprotein accumulation. Conclusion : TSE had antioxidant activity and contained flavonoid, terpenoid, saponin, and steroid. TSE also had low toxicity and histopathologically activity in reducing mucosal damage. It also increased the accumulation of glycoproteins on the mucosal surface.